PENGARUH KELEMBABAN TERHADAP INTENSITAS SERANGAN, AKTIVITAS MAKAN DAN DAYA HIDUP CRYPTOTERMES CYNOCEPHALUS LIGHT. - Ginuk Sumami (Jurnal Penelitian Hasil Hutan, 1988)
A preliminary   study   on  the  effect  of  air humidity   to  infestation   intensity,  feeding  activity   and survival of  the dry- wood  termite  Cryptotermes  cynocephalus   Light,   has been  conducted   by  using flue levels of humidity i.e  37.75%;  70.21%; 83.38%;   87.75%  and 97.0%.The  salts  CaCl2,   NaCl, KCl and K2S04 were  respectively used to control the  air  humidity   of  37.73%  to 87.75%; whereas  H20   was used  to control   the  air humidity   of  97.0%.  Rubber  wood  samples  of  1.5  cm  by  2.5 cm  by  5.0  cm  with a  hole  of  3 cm  by  1 cm  were prepared   to feed  the  termite  workers. The  results  reveal that  the  lowest  feeding activity, infestation   intensity   and  survival   of  the  dry-wood  termite   were indicated   by  the  37.73%  air humidity;   where as the  highest  feeding activity and  survival of  the  termite  were  indicated by  the  90% air humidity.   Meanwhile  there  were no significant   influence   of  infestation   intensity   within   the air  humidity   of  more   than  70%.